Dilematik Sampah di Era Sekarang Dalam Penciptaan Karya Seni Lukis - Niken, Ni Wayan; Ruta, I Made; Pemayun, Tjokorda Udiana Nindhia (Program Studi Seni Murni ISI Bali, 2025)
Work creation report entitled “Waste Dilemma in The Current Era in The Creation of Works of Art”. This idea arose from personal anxiety that every day we found rubbish everywhere. This problem gave rise to a strong urge to present visualizations of various forms of waste, especially plastic waste, in painting. The aim of using waste in this research is to provide an overview of what waste looks like if it is left for too long and accumulates. The method for creating works goes through three stages, namely, direct observation in the field, exploration, and embodiment in a painting. The work will later display realist techniques with a combination of paste as texture such as plastic, dried acrylic paint and scraps of used cardboard. As well as new findings on the texture of wood dust (saw residue). The trash objects are arranged in such a way with splashes or melted accents on each side of the object to attract attention. The game of value (level of brightness or darkness) also plays a very important role in giving dimension and depth to a work of art. The author to realize how trash objects can look very dirty and disgusting. Messy or careless placement makes waste even more unsightly. This aims to make everyone aware of how dangerous an dirty waste is if left to pile up for years on earth.